Morpho-physiological Response of Gliricidia sepium to Seawater-induced Salt Stress - Rahman, MA; Das, AK; Saha, SR; Uddin, MM; Rahman, MM (The Agriculturists, 2019)
Soil degradation due to the contamination of excessive saline water has been threatening soil health vis a vis plant productivity worldwide. Gliricidia sepium, a fertilizer tree, has come into limelight in recent decades in Bangladesh due to its potency in improving soil fertility. However, study on its suitability in coastal areas alongside identifying the salt-endurance limit is still lacking. Therefore, morpho-physiological attributes of G. sepium under seawater-induced different levels of salt stress were analyzed in a pot experiment from March to May 2018 to gain an insight into its salt-adaptive mechanisms. Results revealed that seawater-induced salinity negatively affected the growth-related attributes, such as plant height, fresh weight of shoots, dry weights of shoots and roots, and leaf area. The reduction of growth was coincided with reductions in photosynthetic pigments and relative water content. Interestingly, salt tolerance index was not decreased in parallel with increasing dosages of seawater, indicating the salt tolerance capacity of G. sepium. Furthermore, enhanced accumulation of proline increased the osmoprotective capacity of G. sepium in order to overcome the salt-induced osmotic stress. The results of the present study concluded that G. sepium might be suitable for growing in the salt prone areas ranging 20 – 40 dSm-1. The Agriculturists 2019; 17(1-2) 66-75